Impaired mitochondrial dynamics and mitophagy in neuronal models of tuberous sclerosis complex - Ebrahimi-Fakhari, Darius; Saffari, Afshin; Wahlster, Lara; Kölker, Stefan (Cell reports, 2016)
Tuberous Sclerosis Complex (TSC) is a neurodevelopmental disease caused by TSC1 or TSC2 mutations and subsequent activation of the mTORC1 kinase. Upon mTORC1 activation, anabolic metabolism, which requires mitochondria, is induced, yet at the same time the principal pathway for mitochondrial turnover, autophagy, is compromised. How mTORC1 activation impacts mitochondrial turnover in neurons remains unknown. Here we demonstrate impaired mitochondrial homeostasis in neuronal in vitro and in vivo models of TSC. We find that Tsc1/2-deficient neurons accumulate mitochondria in cell bodies but are depleted of axonal mitochondria, including those supporting presynaptic sites. Axonal and global mitophagy of damaged mitochondria is impaired, suggesting that decreased turnover may act upstream of impaired mitochondrial metabolism. Importantly, blocking mTORC1 or inducing mTOR-independent autophagy restores mitochondrial homeostasis. Our study clarifies the complex relationship between the TSC-mTORC1 pathway, autophagy and mitophagy, and defines mitochondrial homeostasis as a therapeutic target for TSC and related diseases.,